CRIMINAL RESPONSIBILITY OF PERPETRATORS OF ASSAULT JOINTLY RESULTING IN DEATH: STUDY OF DECISION NUMBER 2526/PID.B/2022/PN MDN - Salam, Nazla Abdul (Inspiring Law Journal, 2025)
The crime of assault committed jointly resulting in death is a form of serious crime regulated in Article 170 paragraph (2) 3 of the Criminal Code. This study aims to analyze the legal provisions governing criminal liability for perpetrators of assault jointly and how the principle of individual criminal liability is applied in concrete cases. The method used is normative juridical with a descriptive-analytical approach to Decision Number 2526/Pid.B/2022/PN Mdn. The results of the analysis show that the panel of judges considered the elements of joint violence, the involvement of the perpetrators, and the impacts caused. The defendant was sentenced to 8 years and 6 months in prison. The conclusion of this study is that in cases of collective crime, criminal liability must be determined based on the role of each perpetrator.